Polymorphism of Plasmodium Falciparum Dihydrofolate Reductase and Dihydropteroate Synthase Genes among Pregnant Women with Falciparum Malaria in Banjar District, South Kalimantan Province, Indonesia - Fitriah, Fitriah; Sulistyawati, Sriwijayanti; Riyanto, Sugeng; Budiono, Budiono; Basuki, Sukmawati; Dachlan, Yoes P; Uemura, Haruki (Journal of Tropical Life Science, 2012)
Pregnant women are highly vulnerable to malaria infection in its endemic areas, particularly infection by Plasmodium falciparum that can cause premature, low birth weight, severe anemia in pregnant women, and death. Sulfadoxine-pyrimethamine (SP) for Intermittent Preventive Treatment for pregnant (IPTp) is used for malaria control in pregnancy recommended by the World Health Organization that has already been implemented in Africa. The P. falciparum resistance to SP has been reported in several malarial endemic areas, and mutations in the genes of Plasmodium falciparum Dihydrofolate Reductase (Pfdhfr) and Dihydropteroate Synthase (Pfdhps) are shown to be associated with parasite resistance to SP treatment. Genetic analysis of Pfdhfr and Pfdhps genes in pregnant women infected with P. falciparum has not yet been examined in Indonesia. The cross-sectional study was conducted at two subdistricts, Sungai Pinang and Peramasan, in Banjar district of South Kalimantan Province, where 127 pregnant women were recruited from 2008 to April 2010. Two important mutations in Pfdhfr gene (amino acid positions at N51 and S108) and three in Pfdhps gene (A437, K540 and A581) were analyzed by nested PCR-RFLP method. All of the seven pregnant women samples infected with P. falciparum presented PfDHFR 108N and PfDHPS 437G mutations. One of the samples had the additional mutation at PfDHPS 540, in which Lys is substituted by Glu. These results suggested that P. falciparum might present only some resistance to SP at Sungai Pinang and Peramasan subdistricts, Banjar District, South Kalimantan province, Indonesia. Although there were limited number of samples, this study showed only few mutations of Pfdhfr and Pfdhps genes in P. falciparum at Banjar district, South Kalimantan Province, that suggests SP might be effective for IPTp in this area. Thus, further analysis of the other mutation sites in Pfdhfr and Pfdhps genes and in vivo efficacy study of SP with more sufficient sample numbers will be necessary to confirm this preliminarily result.Keywords: PfDHFR and PfDHPS genes, Pregnant women, Falciparum malaria